Differences in melting temperatures of degenerated oligonucleotides targetting nitrous oxide reductase (nosZ) genes - Stres, Blaž (Acta agriculturae Slovenica, 2008)
One of the basic principles of molecular biology is the use oligonucleotides with comparable melting temperatures (Tm). To accommodate various evolutionary changes in target gene sequences in order to detect numerous variants of the same gene in complex microbial communities, the researchers were forced to design degenerated oligonucleotide probes and primers. In addition, recent studies suggested that relevant parameters influencing microbial activity should be included into models currently describing the final greenhouse gas emissions for public use. Further, data on microbial community structure and abundance should be included as well in near future. As one of the most potent greenhouse gases, nitrous oxide, results mainly from incomplete denitrification process, we chose nitrous oxide reductase gene (nosZ) as a model and surveyed published literature for nosZ gene oligonucleotides. We calculated in-silico Tm for each oligonucleotide degenerated variant and compared the resulting average Tm of both oligonucleotides used in pair. Degenerated oligonucleotides were found to contain variants differing in Tm for as much as 13 °C. More than 85% of oligonucleotides had difference in average Tm of paired oligonucleotide larger than 2 °C, more than 60% larger than 4 °C and more than 40% larger than 6 °C, 25% larger than 8 °C. By using such combinations at one annealing temperature or touch-down PCR or hybridization protocol, the full use of all degenerate variants could never be achieved thus bringing under the consideration the reaction chemistry. To increase the consistency of molecular results, a simple adjustment of Tm to at least comparable average Tm is recommended. In addition, critical evaluation of other methodological pitfalls should be regular practice in order to strengthen the value of molecular results as future public models parameters.
Keywords: microbiology; mikrobiologija; molecular biology; molekularna biologija; taljenje; temperatura; oligonucleotidi; toplogredni plini